The Meaning of Love - Garlikov, Richard; Open Textbook Library (Open Textbook Library, 2017)
This book explores the philosophical views on the meaning of love. The text explores a variety of topics used to define love, including attraction, relationship satisfaction, emotional, and ethical considerations. The author takes a rational, logical, analytic, and scrutinizing look at experiences and other forms of literature on the subject of love.
Dedication and AcknowledgementsDisclaimerA Note Concerning GrammarIntroduction -- Chapter 1 Personal Versus Professional Relationships -- Chapter 2 Love, Some Popular Views -- Chapter 3 The Three Important Aspects of Relationships -- Chapter 4 The Emotional Aspect- Feelings -- Chapter 5 The Satisfaction Aspect -- Chapter 6 The Goodness and Badness (Ethical) Aspect -- Chapter 7 Independence of the Three Aspects of Relationships -- Chapter 8 The Meaning of Love -- Chapter 9 Infatuation, Friendship, and Love -- Chapter 10 Love at First Sight -- Chapter 11 Importance of Various (Kinds of) Satisfactions -- Chapter 12 Sex and Love -- Chapter 13 A Kiss Is Just a Kiss - The Impossibility of Sexual Communication -- Chapter 14 Being Loved For Yourself -- Chapter 15 Loving More Than One Person At the Same Time -- Chapter 16 Commitment and Loving More Than One Person -- Chapter 17 Rejection and Acceptance -- Chapter 18 Care and Concern -- Chapter 19 Love and Marriage -- Chapter 20 The Future of a Relationship -- Chapter 21 Love and Change and Rational Prediction -- Chapter 22 Jealousy -- Chapter 23 Independence and Sharing -- Chapter 24 "Meaningful" Relationships -- Chapter 25 Introduction to Ethics -- Chapter 26 Ethics - Seeking to Discover What the Highest Principles of Behavior and the Things of Greatest Value Are -- Chapter 27 Modification of the Analysis of Love -- Chapter 28 Good "For" and Good "To" -- Chapter 29 Ethical Principles and Spontaneity -- Chapter 30 Ethics and Sex -- Chapter 31 Sex and Intimacy -- Chapter 32 Relationships After Sex -- Chapter 33 Problems of the Inexperienced -- Chapter 34 On Being Used -- Chapter 35 The Causes of Feelings -- Chapter 36 Some Other Writers on Love -- Chapter 37 Some Personal Comments and Notions of a More Intuitive Nature -- GlossaryReferences
In English.
Description based on print resource
Keywords: Social sciences -- Textbooks